Design framework and consideration for urban mosques in Kuala Lumpur as a model of compact city - Sarram, Arman (2017)
For every Muslim community mosque is vital part of the daily life. Since the early period of mosques’ establishment, the institution had been through changes in its planning and design to adopt the contextual requirements of the expanding Islamic territories. Thousands of years after the creation of Islam’s place of worship, issues and problems of its continuous establishment stemming from complexity of modern living has forced urban planners and architects to reconsider its planning and implementation in regard with limited land availability, shortage of resources, accessibility and appropriate architectural expression. Which results a deviation from the usual architectural conventions while faced with the challenge of retaining the integrity of its fundamental functionality, purpose and appropriateness. This study provides insight on the merits as well as the challenges of modern day planning, executing and building of mosque in urban areas. The study focuses particularly on compact cities where the issue of land insufficiency and resource shortage is most intense. Information of the selected mosques within the chosen areas are based on collected primary and secondary data which are specifically based on the (1) layout and capacity of the mosque, (2) facilities provided by the mosque and (3) activities within the mosque. Primary data was collected from three mosques within the city of Kuala Lumpur. Secondary data are collected from three different sites from several countries were considered for this study all of which are situated inside compact cities and have high density of population. The study adopts qualitative research strategy with the focus on interview and observation as data collection method. The selected mosque for secondary data from foreign countries are Ishtiqlal Mosque, Jakarta, Indonesia; Kowloon Mosque, Hong Kong; Masjid Al-Islah, Punggol, Singapore and the selected mosque within Kuala Lumpur are Majid Al Imam Asy-Syafei, Masjid Jamek Kg. Baru and Masjid Jamek Pakistan. Outcome of this research proposes appropriate definition for urban mosques in compact cities, especially for the city of Kuala Lumpur. The research also found that every mosque in compact cities must consider some factors such as, (1) vertical development with integrated spaces, (2) visual and physical connections both horizontally and vertically, (3) accessibility in design, (4) flexible spaces designed for multipurpose activities, (5) providing plaza areas to avoid congestion in design and (6) use of online media to reach out to the community without necessitating to be physically present for basic information. This study evaluates the viability of urban mosque in compact city setting to learn further on the efficient utilization of space and how structures such as mosque can function optimally in its capacity to serve its purpose for the population. Hence this study supplements to current knowledge of planning mosque in compact cities by proposing design framework for optimal spatial utilization. Further studies on this topic are recommended for better understanding and more specific guideline for developing urban mosques in compact cities.